Detection of changes in dynamic characteristics of composite structures using Kriging metamodeling procedure: Experimental and computational analysis - Possenti K.A.* (2023)
© 2023 Taylor & Francis Group, LLC.To ensure the quality, safety, and long-term durability of fiber-reinforced composite components, it is necessary to explore approaches for monitoring and detecting defects or damage. Nondestructive detection techniques based on dynamic properties and structural response, such as natural frequency, damping, and modal shape. This study presents a numerical-experimental methodology based on dynamic analysis of structures made of composite materials. The methodology utilizes a surrogate model to establish a design envelope through a Kriging metamodel and to assess a damage index for structures affected by impact damage. The Latin Hypercube method is employed to generate values for the input variables, while the finite element method is utilized to calculate the natural frequencies. The Kriging metamodel is then employed to generate a numerical model, which is optimized using the Efficient Global Optimization algorithm and the expected improvement metric to minimize computational costs. The methodology yields a frequency range and determines a design envelope to evaluate the manufacturing quality of the structure. A damage index is used to identify structures with defects or impact damage, allowing for the assessment of severity. Additionally, the study evaluates the impact of incorporating metrics into the Latin Hypercube method to further reduce computational costs. Finally, this proposed approach contributes to the development of monitoring systems for assessing the manufacturing quality of composite structures and detecting impact damage through dynamic analysis. By utilizing this methodology, it becomes possible to effectively identify and evaluate the severity of defects and damage in composite structures, thus enhancing quality evaluation processes.